Case study of disseminated leiomyomatosis with urological and colorectal involvement and a literature review - Habib, Dato Outban; Rebbani, M.; Akhdamch, A.; Kaid, Kaid M.; Moctar, Noufou Fodiya; Yaka, M.; Njoumi, N.; Fahssi, M. El; Hajjouji, A. El; Ali, Abdelmounaim Ait (International Surgery Journal, 2024)
Disseminated peritoneal leiomyomatosis (DPL), also known as diffuse peritoneal leiomyomatosis, is a rare disease characterized by a sub peritoneal proliferation of benign nodules, mainly composed of benign smooth muscle cells, macroscopically mimicking peritoneal carcinosis. We report the case of a 60-year-old patient, with hypertension under treatment, being followed for the management of pauci-symptomatic abdominopelvic masses, evolving in a context of conservation of the general state, who underwent hysterectomy with adnexectomy by laparotomy for uterine myoma. Imaging revealed three masses, extending from the perigastric to the pelvic region, with areas of necrosis, moderate peritoneal effusion and lumbo-aortic and primitive iliac lymph nodes with small infracentimetric axes. The management consisted of a complete cytoreduction. Postoperative management was straightforward. LPD is a rare condition, with around 200 cases published in the literature. Its incidence is estimated at around 1/10,000,000, given the generally asymptomatic nature of the disease. The etiopathogenesis of this condition remains poorly elucidated, although several causal theories have been described in the literature, including hormonal, iatrogenic and congenital or hereditary. The management of LPD is not currently standardized, but surgery remains the gold standard. LPD is a rare, benign condition characterized by sub peritoneal proliferation of smooth muscle cells. It occurs most frequently in women of childbearing age, but can also occur in postmenopausal women and men. Treatments for LPD are not standardized, and further studies are required in the near future.